Endometriosis-associated Ovarian Cancer, from Risk Factors to Survival Rate: A Systematic Review and Meta-Analysis - Elham Askary; Saeed Alborzi; Kefayat Chamanara; Alimohammad Keshtvarz Hesam Abadi (Middle East Journal of Cancer)
Background: Endometriosis experts recommend monitoring patients until menopause before considering surgery, with concerns about lesion malignancy. This meta-analysis aims to assess the prevalence and prognosis of endometriosis-associated ovarian cancer (EAOC) in various types of epithelial ovarian cancer (EOC), and compare risk factors with the non-EAOC group to improve disease management.Method: In this review, PubMed, Science Direct, Scopus, Google Scholar, and Cochrane databases were searched for "endometriosis" and "ovarian cancer risk factor" from 2010 to 2023. Papers not reporting cancer prevalence or without a specified sample size were excluded. The study used statistical Cochran's Q and I2 index tests to evaluate heterogeneity and estimate ovarian cancer prevalence. Odds ratio was used to explore risk factors for cancer development.Results: In our meta-analysis of 20 studies, 31,667 women with Non-EAOC were compared with 2826 women with EAOC across various factors: EOC subtypes, age, parity, menopausal status, FIGO stage, 5-year survival rate, and Ca125 levels. In our study, EAOC exhibited a 7.34% cancer incidence. While clear cell and endometrioid types were more common in EAOC than in the non-EAOC group, the low-grade serous type was the most prevalent malignancy.Patients with early-stage EAOC have a 1.7 times higher 5-year survival rate compared with non-EAOC groups. EAOC is more common in nulliparous (2.243 times) and premenopausal women (2.169 times), but the CA125 levels are not significantly different between the groups.Conclusion: Based on data and positive outlook, careful monitoring, considering medical history, and avoiding early surgery are highly recommended in endometriotic patients.